Topical Tenofovir Pre-exposure Prophylaxis and Mucosal HIV-Specific Fc-Mediated Antibody Activities in Women - Fisher, Kimone Leigh; Mabuka, Jennifer M.; Sivro, Aida; Ngcapu, Sinaye; Passmore, Jo-Ann Shelley; Osman, Farzana; Ndlovu, Bongiwe; Abdool Karim, Quarraisha; Abdool Karim, Salim S.; Chung, Amy W.; Baxter, Cheryl; Archary, Derseree (Frontiers in Immunology, 2020)
The RV144 HIV-vaccine trial highlighted the importance of envelope-specific non-neutralizing antibody (nNAb) Fc-mediated functions as immune correlates of reduced risk of infection. Since pre-exposure prophylaxis (PrEP) and HIV-vaccines are being used as a combination prevention strategy in at risk populations, the effects of PrEP on nNAb functions both mucosally and systemically remain undefined. Previous animal and human studies demonstrated reduced HIV-specific antibody binding avidity post-HIV seroconversion with PrEP, which in turn may affect antibody functionality. In seroconverters from the CAPRISA004 tenofovir gel trial, we previously reported significantly higher detection and titres of HIV-specific binding antibodies in the plasma and genital tract (GT) that distinguished the tenofovir from the placebo arm. We hypothesized that higher HIV-specific antibody titres and detection reflected corresponding increased antibody-dependent neutrophil-mediated phagocytosis (ADNP) and NK-cell-activated antibody-dependent cellular cytotoxic (ADCC) activities. HIV-specific V1V2-gp70, gp120, gp41, p66 and p24 antibodies in GT and plasma samples of 48 seroconverters from the CAPRISA004 tenofovir gel trial were tested for ADCP and ADCC at 3, 6- and 12-months post-HIV-infection. GT gp41- and p24-specific ADNP were significantly higher in the tenofovir than the placebo arm at 6 and 12 months respectively (p<0.05). Plasma gp120-, gp41- and p66-specific ADNP, and GT gp41-specific ADCC increased significantly over time (p<0.05) in the tenofovir arm. In the tenofovir arm only, significant inverse correlations were observed between gp120-specific ADCC and gp120-antibody titres (r=-0.54; p=0.009), and gp41-specific ADNP and gp41-specific antibody titres at 6 months post-infection (r=-0.50; p=0.015). In addition, in the tenofovir arm, gp41-specific ADCC showed significant direct correlations between the compartments (r=0.53; p=0.045). Certain HIV-specific nNAb activities not only dominate specific immunological compartments but can also exhibit diverse functions within the same compartment. Our previous findings of increased HIV specific antibody detection and titres in women who used tenofovir gel, and the limited differences in nNAb activities between the arms, suggest that prior PrEP did not modulate these nNAb functions post-HIV seroconversion. Together these data provide insight into envelope-specific-nNAb Fc-mediated functions at the site of exposure which may inform on ensuing immunity during combination HIV prevention strategies including PrEP and HIV vaccines.